Problematika Tafsir Sosial Dawam Rahardjo: Kritik Atas Etika dan Metodologi Penafsiran al-Qur`an - Syafirin, Muhammad (STAI Darul Kamal NW Kembang Kerang, 2024)
The development of Qur'anic studies in Indonesia, especially in the 90s, experienced significant growth. It was marked by the emergence of various methodological offers from those who not only specialize as mufassirs, but also from non-mufassir scholars. Dawam Rahardjo with his new idea of “social thematic interpretation” (al-Mauḍū’īyyah al-Ijtimā’iyyah) is one of the non-interpretive scholars who have colored the dialectic of Qur`anic interpretation. His thematic methodology based on the analysis of key terms has become an object of discourse that continues to be debated until now. The research in this article is one of the critical studies that tries to fill the discourse. Methodologically, this research is a qualitative research that is operationalized in two approaches: First, the historical approach is used to analyze the originality of the development of Dawam Rahardjo’s tafsir thought. Second, through a critical approach from the perspective of ‘ulūm al-Qur`ān, the author rethinks and critically reads Dawam Rahadjo's interpretation methodology, both in terms of novelty, excellence and weakness. The results of this study show that Dawam Rahardjo’s thematic interpretation methodology has no fundamental differences with thematic methods in general, although some aspects such as “historical interpretation” and “paradigmatic interpretation” are distinctive. However, Dawam has some weaknesses. In terms of the ethics of interpretation, he tends to be apathetic towards the “formal requirements” agreed upon by the majority of scholars, thus often ignoring the basic principles in interpretation. While in terms of methodology, his ideas are still discursive discourse, immature, so it is not uncommon when interpreting, his ideas are not in line with the theory he developed, even some aspects of his views seem distorted, especially his description of the genealogy of thematic interpretation (mauḍū’ī).